Gold Nanoparticles on 3D-Printed Filters: From Waste to Catalysts - Lahtinen, Elmeri (ACS Omega, 2019)
[Image: see text] Three-dimensionally printed solid but highly porous polyamide-12 (PA12) plate-like filters were used as selective adsorbents for capturing tetrachloroaurate from acidic solutions and leachates to prepare PA12–Au composite catalysts. The polyamide-adsorbed tetrachloroaurate can be readily reduced to gold nanoparticles by using sodium borohydride, ascorbic acid, hydrogen peroxide, UV light, or by heating. All reduction methods led to polyamide-anchored nanoparticles with an even size distribution and high dispersion. The particle sizes were somewhat dependent on the reduction method, but the average diameters were typically about 20 nm. Particle sizes were determined by using a combination of single-particle inductively coupled plasma mass spectrometry, helium ion microscopy, and powder X-ray diffraction. Dispersion of the particles was analyzed by scanning electron microscopy with energy-dispersive spectroscopy. Due to the high adsorption selectivity of polyamide-12 toward tetrachloroaurate, the three-dimensional-printed filters were first used as selective gold scavengers for the acidic leachate of electronicwaste (WEEE). The supported nanoparticles were then generated directly on the filter via a simple reduction step. These objects were used as catalysts for the reduction of 4-nitrophenol to 4-aminophenol. The described method provides a direct route from waste to catalysts. The selective laser sintering method can be used to customize the flow properties of the catalytically active filter object, which allows the optimization of the porous catalytic object to meet the requirements of catalytic processes.